SMART GATEKEEPER: SISTEM PINTU MASUK CERDAS UNTUK PERPUSTAKAAN DENGAN KONTROL SUARA DAN PENGHITUNG OTOMATIS - Tholib Hariono; Moh Zuem Marzuki (JURNAL ILMIAH NUSANTARA, 2025)
This research develops "Smart Gatekeeper," a smart entrance system for automating library visitor monitoring. The system integrates an ESP32 microcontroller with a pair of infrared (IR) sensors for automatic visitor counting and a voice recognition module for basic interaction. Visitor data is displayed in real-time on an LCD and archived in a MySQL database for further analysis, while a DFPlayer Mini module provides voice feedback. System testing shows a 100% accuracy rate in detecting visitor traffic. The implementation of "Smart Gatekeeper" successfully improves efficiency, data accuracy, and adds a modern touch to library services.